Predictive Role of Personality Traits, Alcohol Use and Emotion Regulation on Dangerous Driving Behaviour among Commercial Drivers in Yenagoa, Nigeria - Otoghile, Confidence Chioma; Azikiwe, Judith Chineye; Olatunji, O. Ajoke; Oladejo, Teslim Alabi (African Journal of Stability and Development (AJSD), 2025)
Dangerous driving among commercial drivers has become more pronounced in contemporary times, as there tends to be an increase in road traffic accidents in Nigeria, according to available reports. The reasons for this increase are yet to be fully explored. Some psychosocial factors may be implicated in this recent occurrence. There is a gap in knowledge, as these psychosocial factors have not been studied enough. The study investigated the predictive role of personality traits, alcohol use, and emotion regulation on dangerous driving behaviour among commercial drivers in Yenagoa. The study adopted a cross-sectional survey. The sample size for the study was 300. Eysenck questionnaire, Alcohol Use Disorder Identification Test, Emotion Regulation questionnaire and Dula Dangerous Driving Index were used to assess personality traits, alcohol use, emotion regulation and dangerous driving, respectively, in this study. Multiple linear regression was used to test the hypothesis. Results showed that personality traits, alcohol use, and emotion regulation independently and jointly (R2 = .314, F = [3, 296] = 45.08; p<.01) predicted dangerous driving behaviour among commercial drivers. It was concluded that personality traits, alcohol use, and emotion regulation significantly influence hazardous driving behaviour.